2017
DOI: 10.1021/acs.energyfuels.7b01588
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Upgrading of Heavy Oils via Solvent Deasphalting Using Asphaltene Precipitants. Preparative Separations and Mechanism of Asphaltene Precipitation Using Benzoyl Peroxide as Precipitant

Abstract: Subsurface upgrading of heavy oil via solvent deasphalting has been reported previously under laboratory and field conditions. However, these processes require a relatively high solvent-to-oil ratio (SvOR > 1:1 v/v) to induce subsurface asphaltene precipitation, increase oil production, and upgrade crude oil in situ. In our previous work, lab experiments demonstrated that asphaltene precipitants reduce the SvOR (∼30−50 vol %) for subsurface upgrading at initial reservoir conditions and when heat is also applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A ratio of 13 (mL n C5/ g VR) was, thus, routinely selected for laboratory operation with 5 L flasks. Lower solvent/samples ratios like those described in the open literature (ratios around 5), , were not herein attempted because the filtering procedure required for asphaltenes isolation became very difficult at high viscosity. Routine standardized laboratory-scale deasphalting is carried out at a large solvent/sample ratio (around 30) for facilitating manual operation and improving the test repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…A ratio of 13 (mL n C5/ g VR) was, thus, routinely selected for laboratory operation with 5 L flasks. Lower solvent/samples ratios like those described in the open literature (ratios around 5), , were not herein attempted because the filtering procedure required for asphaltenes isolation became very difficult at high viscosity. Routine standardized laboratory-scale deasphalting is carried out at a large solvent/sample ratio (around 30) for facilitating manual operation and improving the test repeatability.…”
Section: Resultsmentioning
confidence: 99%
“…There is circumstantial evidence that supports asphaltene molecules exhibiting pancake bonding. For example, Rogel et al found the addition of radical initiator (benzoyl peroxide) led to a ∼21 wt % increase in the precipitated asphaltene content . If pancake bonding promoted by radicals is a key contributor to asphaltene aggregation, we would expect that it would result in a shorter packing distance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rogel et al found the addition of radical initiator (benzoyl peroxide) led to a ∼21 wt % increase in the precipitated asphaltene content. 134 If pancake bonding promoted by radicals is a key contributor to asphaltene aggregation, we would expect that it would result in a shorter packing distance. The packing distance in π−π stacking is bound by a vdW distance of 3.6 Å.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of nitric acid (HNO 3 ) (67–70% w/w, 5 mL) and hydrogen peroxide (30% w/w, 2 mL) was used in a UltraWAVE microwave sample preparation system (Milestone Inc., USA). 51 For this procedure, 13 samples and two quality controls can be run simultaneously and the whole process (weighing, loading into MW device, MW program, final dilution with internal standard spiking) would take up to 160 min. The carbon, hydrogen, and nitrogen elemental analysis was carried out by flash combustion with a thermal conductivity sensor using Carlo Erba instrument model NT2500 (Hindley Green, UK).…”
Section: Methodsmentioning
confidence: 99%